'It's just one of those natural progressions': Stories of relocating to neighbourhoods of high and low walkability. (May 2021) - Whybrow, Paul; Bramley, G.; Brown, Caroline
Abstract: Walkable neighbourhood characteristics, such as connectivity and land use mix, have been found to correlate with people walking more and being active. However, the relationship between the built environment and behaviour is highly complex making it difficult to develop generalisable and predictive models. This paper reports qualitative findings from 21 in-depth interviews conducted with urban residents who had relocated between neighbourhoods of high and low walkability. Participants' preferences are reported within key domains ( shop access, green space and travel links ). These reveal that walkable characteristics were preferred and desired regardless of whether the participant had moved to a high or low walkable area. We contrast surface preferences with an analysis of relocation stories : complex assemblages of biographical narratives, identity work and cultural representations. The findings reveal how neighbourhood types are consistently associated with life stages and that moving to a suburban home was felt to be a definitive type of relocation in which it was acceptable to put neighbourhood preferences aside. Residential self-selection is not yet properly understood and we recommend studies of relocation stories for examining the sociocultural meanings that are likely to inform relocation decisions. Highlights: Walkable characteristics were desirable regardless of where participant moved. Relocations were complex and not reducible to discrete decisions or preferences. 'Relocation stories' were identified as complex assembles of biography, identity and culture. Sociocultural associations exist between neighbourhood types and life-stages 9.